Analysis of the determinants and typology of hydrometeorological disaster in Sukajaya Subdistrict, Bogor Regency, West Java, Indonesia - Yossa Istiadi; Dolly Priatna (Indonesian Journal of Applied Environmental Studies, 2021)
The objective of this research is to determine the factors as a typology of hydrometeorological disasters. The research method employed is post-disaster survey activities through hypothetical descriptions from October to December 2020. The analysis technique uses factor analysis on five variables, namely runoff, infiltration, slope, land cover, and infrastructure. The data retrieval obtained nine areas of landslide disaster points along 20 kilometers from Kiarapandak Village to Cisangku Village, Sukajaya Subdistrict, Bogor Regency, one of which were the areas affected by landslides in January 2020. From the factorial analysis results, it was found that the five variables above were suitable as a factor for determining disaster based on correlation values (r), that includes Factor 1 which is the variable of land slope (0.855) and the infrastructure variable (0.872). Factor 2 is water infiltration (0.928), water runoff (0.269), and land cover (0.717). In conclusion, the typology of hydrometeorological disasters is distinguished based on two determinants, firstly the physical construction of land, slopes, as well as infrastructure of road and river. Secondly,  factors of water flow, water infiltration, runoff, and land cover.Tujuan penelitian adalah membuat determinasi faktor-faktor sebagai tipologi kebencanaan hidrometeorologi. Metode penelitian melalui kegiatan survey pasca bencana melalui deskripsi hipotetik pada bulan Oktober-Desember 2020. Teknik analisis menggunakan analisis faktor pada 5 (lima) variabel yaitu limpasan, resapan, kemiringan, tutupan lahan, dan infrastruktur. Pengambilan data mendapatkan 9 (sembilan) daerah titik bencana longsor sepanjang 20 kilometer dari Desa Kiarapandak sampai Desa Cisangku, Kecamatan Sukajaya Kabupaten Bogor, yang merupakan wilayah terkena bencana longsor pada bulan Januari 2020. Dari hasil analisis faktorial diperoleh bahwa 5 (lima) variabel di atas layak dijadikan faktor determinasi kebencanaan berdasarkan nilai korelasi (r),  meliputi Faktor 1 adalah variabel kemiringan lahan (0,855) dan variabel infratruktur (0,872). Faktor 2 adalah resapan air (0,928), limpasan air (0,269), dan tutupan lahan (0,717). Kesimpulan, tipologi bencana hidrometeorologi dibedakan berdasarkan dua faktor determinasi yaitu pertama faktor konstruksi fisik lahan, kemiringan dan infratruktur jalan dan sungai, dan faktor aliran air, resapan air, limpasan, dan tutupan lahan.